A throttle-less single rod hydraulic cylinder positioning system for switching loads. (July 2015) - Jalayeri, Ehsan; Imam, Ahmed; Sepehri, Nariman
Abstract: This paper proposes a low-cost, high precision and efficient throttle-less hydraulic circuit that utilizes off-the-shelf industrial elements to control single rod hydraulic cylinders. The circuit uses an on/off solenoid valve to redirect the differential flow of a single rod hydraulic cylinder, and two counterbalance valves to manage switching (resistive–assistive) loads. Conducted experiments on a prototype system indicated a maximum steady state positional error of 0.2 mm. The circuit consumes only 20% of energy that is required by a valve controlled circuit to follow the same tracking signal. A simple proportional controller, that uses readings of a linear position transducer, is employed for all experiments, which makes the designed circuit easy to be implemented.